Bulk superconductor and method for manufacturing bulk superconductor
Patent Information
- Application Number
- JP2021156060
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-24
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-09-24
AI Technical Summary
【0031】 本発明の一態様によれば、鉄系化合物の超伝導バルク体において、従来よりも臨界電流密度を向上させることができる。
Smart Images

Figure 0007642945000002 
Figure 0007642945000003 
Figure 0007642945000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a bulk superconductor and a method for producing a bulk superconductor. [Background technology]
[0002] A bulk superconductor, which is a polycrystal of an iron-based compound that exhibits superconductivity, is known. For example, Patent Document 1 discloses Ba 0.6 K 0.4 The superconducting bulk of Fe2As2 has been described. 0.6 K 0.4 Iron-based compounds in which part of Ba has been replaced with K, such as Fe2As2, are called K-doped Ba122.
[0003] Such a bulk superconductor can capture magnetic flux by cooling in a magnetic field, and therefore functions as a magnet. A magnet using such a bulk superconductor can be used as a magnetic field source in, for example, a magnetic resonance imaging (MRI) device using the Nuclear Magnetic Resonance (NMR) method. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Special Publication No. 2018-512737 Summary of the Invention [Problem to be solved by the invention]
[0005] In Patent Document 1, starting materials are prepared so that the molar ratio of Ba, K, Fe, and As is 0.6:0.42:2:2, and a temporary sintered body of K-doped Ba122 is obtained by hot isostatic pressing (HIP). Next, the sintered body is powdered by milling, and the powdered K-doped Ba122 is pelletized by cold isostatic pressing (CIP). Next, the pellets of K-doped Ba122 are wrapped in silver foil and inserted into a steel tube, and CIP is performed. The diameter of the steel tube containing the sample is reduced by about 10% by this CIP. Next, a final sintered body of K-doped Ba122 is obtained by HIP. In the following, the process of obtaining the final sintered body of K-doped Ba122 is called the main sintering process, and the final sintered body obtained by this manufacturing method is called a superconducting bulk body.
[0006] Thus, when HIP is used in the sintering process, the critical current density of the manufactured superconducting bulk is clearly lower than the critical current density of a single crystal of an iron-based compound exhibiting superconductivity. From this, it can be said that the superconducting bulk manufactured by the manufacturing method using HIP in the sintering process does not fully realize the potential of the iron-based compound exhibiting superconductivity. In other words, there is room to increase the critical current density of conventional superconducting bulk iron-based compounds.
[0007] In addition, sintering methods other than HIP that can be used in this sintering process include the Spark Plasma Sintering (SPS) method and the hot pressing method. However, even when the SPS or hot pressing method is used in this sintering process, the critical current density of the obtained superconducting bulk body is obviously lower than the critical current density of the single crystal of the iron-based compound that exhibits superconductivity, just as in the case of using HIP in this sintering process.
[0008] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to improve the critical current density in a superconducting bulk body of an iron-based compound compared to the conventional art. [Means for solving the problem]
[0009] In order to solve the above problems, a superconducting bulk according to a first aspect of the present invention is a polycrystal of an iron-based superconductor, and has a degree of c-axis orientation of 0.2 or more according to the Lotgering method.
[0010] According to this configuration, since the multiple crystal grains in the superconducting bulk are aligned with a high degree of orientation, the suppression of the critical current density caused by the randomness of the crystal orientation is reduced, and therefore the superconducting bulk can effectively utilize the potential of the single crystal of the iron-based superconductor and exhibit a critical current density improved over the conventional one.
[0011] A second aspect of the present invention relates to a bulk superconducting body according to the first aspect described above, wherein the degree of orientation is 0.4 or more.
[0012] With this configuration, the superconducting bulk material can better utilize the potential of the single crystal of the iron-based superconductor, and can exhibit a critical current density that is improved compared to the past.
[0013] A superconducting bulk body according to a third aspect of the present invention is the first or second aspect described above, which has a disk-like shape and in which the normal direction of the main surface corresponds to the orientation direction of the c-axis.
[0014] With this configuration, it is possible to further improve the critical current density when the superconducting bulk body captures magnetic flux so as to be magnetized along the normal direction.
[0015] A fourth aspect of the present invention relates to a bulk superconducting body according to the third aspect described above, the bulk superconducting body having a thickness of 1 mm or more.
[0016] With this configuration, it is possible to realize a superconducting bulk body having mechanical strength suitable for practical use as a superconductor, for example, a superconducting bulk magnet.
[0017] A bulk superconductor according to a fifth aspect of the present invention is any one of the first to third aspects described above, and contains at least one element selected from tin, gallium and indium.
[0018] According to this configuration, the low-melting point metal strengthens the electrical bonds between crystal grains at the grain boundaries, thereby further improving the critical current density of the superconducting bulk body.
[0019] A sixth aspect of the present invention relates to a superconducting bulk body in accordance with the first to fifth aspects described above, wherein the iron-based superconductor is a compound represented by the chemical formula AeAFe4As4, where Ae is at least one element selected from Ca, Sr, and Ba, and A is at least one element selected from K, Rb, and Cs.
[0020] According to this configuration, the single crystal of the iron-based superconductor exhibits a high critical current density, and therefore the polycrystalline superconducting bulk also exhibits a high critical current density.
[0021] A manufacturing method according to a seventh aspect of the present invention is a method for manufacturing a superconducting bulk body which is a polycrystal of an iron-based superconductor, and includes a sintering step in which a pellet which is a pre-sintered body is sintered while applying uniaxial pressure along the normal direction of the main surface and so that the ratio of the main surface size of the pellet to the thickness of the pellet is increased, thereby obtaining the superconducting bulk body.
[0022] This configuration promotes the formation of an oriented structure of the crystal grains contained in the pellet, which makes it possible to produce a bulk superconductor that fully utilizes the potential of the single crystal of the iron-based superconductor and exhibits a higher critical current density than ever before.
[0023] A manufacturing method according to an eighth aspect of the present invention is the same as that of the seventh aspect described above, wherein in the main sintering process, the pellet is sintered while being uniaxially pressed in a cavity, and the cavity size of the cavity is larger than the main surface size.
[0024] According to this configuration, the pellet is deformed by uniaxial pressure so as to elongate along the tangential direction of the main surface, which promotes the alignment of the crystal grains inside the pellet, and therefore improves the degree of orientation of the crystal grains in the resulting bulk superconductor.
[0025] A manufacturing method according to a ninth aspect of the present invention is the same as the seventh or eighth aspect described above, in which the pellets are sintered while being uniaxially pressed by using a spark plasma sintering method or a hot press method.
[0026] According to this configuration, it is possible to realize the sintering process which is suitable for both small-scale and large-scale production and requires low equipment costs.
[0027] A tenth aspect of the present invention relates to the production method of any one of the seventh to ninth aspects described above, wherein the pellet contains at least one element selected from tin, gallium and indium.
[0028] With this configuration, the low-melting point metal acts as a lubricant to promote the alignment of crystal grains, and in the resulting superconducting bulk, the electrical bonding between crystal grains at the grain boundaries is strengthened, thereby further improving the critical current density of the superconducting bulk.
[0029] The manufacturing method according to an eleventh aspect of the present invention is, in any one of the seventh to tenth aspects described above, wherein the pellet contains a compound represented by the chemical formula AeAFe4As4, where Ae is at least one element selected from Ca, Sr, and Ba, and A is at least one element selected from K, Rb, and Cs.
[0030] With this configuration, the manufacturing process is simplified and the bulk superconductor can be manufactured at low cost. Effect of the Invention
[0031] According to one aspect of the present invention, in a superconducting bulk of an iron-based compound, the critical current density can be improved as compared to the conventional case. [Brief description of the drawings]
[0032] [Figure 1] 1A is a perspective view showing a superconducting bulk material according to a first embodiment of the present invention, and FIG. 1B is a cross-sectional view showing a schematic diagram of the superconducting bulk material shown in FIG. [Diagram 2] 2 is an oblique view showing the crystal structure of a compound constituting the crystal grains contained in the superconducting bulk body shown in FIG. 1. [Diagram 3] 10 is a flowchart showing the flow of a manufacturing method according to a second embodiment of the present invention. [Figure 4] (a) is a cross-sectional view showing a pellet after a pre-sintering step included in the manufacturing method shown in FIG. 3. (b) is a cross-sectional view showing a pellet before a main sintering step included in the manufacturing method shown in FIG. 3. (c) is a cross-sectional view showing a superconducting bulk body after the main sintering step described above. (d) is a cross-sectional view showing a pellet obtained by the pre-sintering step described above. (e) is a cross-sectional view showing a superconducting bulk body obtained by the main sintering step described above. [Diagram 5] 1 is a graph showing X-ray diffraction (XRD) patterns of the superconducting bulk bodies of the first and second examples of the present invention, the piece of the first reference example, the pellet of the first comparative example, and the powder of the second comparative example. [Figure 6] The upper part shows an SEM image and an EBSD map of a cross section of the pellet of the first comparative example shown in Fig. 5. The lower part shows an SEM image and an EBSD map of a cross section of the bulk body of the second example shown in Fig. 5. [Figure 7] The upper part shows an SEM image and an EDX map of a cross section of the pellet of the first comparative example shown in Fig. 5. The lower part shows an SEM image and an EDX map of a cross section of the bulk body of the second example shown in Fig. 5. [Figure 8] 6 is a graph showing the applied magnetic field dependence of the critical current density exhibited by the superconducting bulk of the second embodiment shown in FIG. 5 and the pellet of the first comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0033] [First embodiment] A superconducting bulk body B according to a first embodiment of the present invention will be described with reference to Figures 1 and 2. Figure 1(a) is a perspective view showing a superconducting bulk body B according to the first embodiment of the present invention, and Figure 1(b) is a cross-sectional view showing a schematic diagram of the superconducting bulk body B shown in Figure 1(a). Figure 2 is a perspective view showing the crystal structure of a compound 10 constituting a crystal grain 1 contained in the superconducting bulk body B shown in Figure 1.
[0034] <Compound Overview> As shown in FIG. 1(b), the superconducting bulk B is a polycrystal containing a plurality of crystal grains 1. Each of the crystal grains 1 is composed of a single crystal of compound 10. Compound 10 is an iron-based superconductor that exhibits superconductivity in a temperature range below the critical temperature Tc. Therefore, the superconducting bulk B, which is a polycrystal of compound 10, exhibits superconductivity in a temperature range below the critical temperature Tc, similar to compound 10.
[0035] (Chemical formula of compound) Compound 10 is a compound represented by the chemical formula AeAFe4As4. In the formula, Ae is at least one element selected from Ca, Sr, and Ba, and A is at least one element selected from K, Rb, and Cs. In this embodiment, Ca is selected as Ae, and K is selected as A. A single crystal made of the compound represented by the chemical formula AeAFe4As4 exhibits a high critical current density Jc, and therefore, this compound is preferable as compound 10.
[0036] (Crystal structure of the compound) With reference to FIG. 2, the crystal structure that compound 10 can have will be described. Compound 10, which is a compound represented by the chemical formula AeAFe4As4, can have a crystal structure in which AeFe2As2 layers 16 and AFe2As2 layers 17 are alternately stacked along the c-axis, as shown in FIG. 2. The AeFe2As2 layer 16 is composed of Ae sites 11, Fe sites 13, and As sites 14. The AFe2As2 layer 17 is composed of A sites 12, Fe sites 13, and As sites 15. The crystal structure shown in FIG. 2 has a space group of simple tetragonal P4 / mmm and has a CaRbFe4As4 structure. The crystal structure of compound 10 has anisotropy.
[0037] The crystal grain 1 resulting from the growth of such a crystal structure typically has a plate-like shape in which a layered structure stacked along the c-axis extends along the ab-plane. In other words, the crystal grain 1 has anisotropy, and the normal direction of the main surface of the plate-like shape coincides with the c-axis of the crystal structure, and the tangent direction of the main surface coincides with the ab-plane of the crystal structure.
[0038] (Another composition of the compound) In addition, the compound 10 is not limited to the compound represented by the above-mentioned chemical formula AeAFe4As4, but may be any compound that contains an Fe element and exhibits superconductivity in a temperature range below the critical temperature Tc. A superconducting compound containing an Fe element has anisotropy in its crystal structure. Since a single crystal made of the compound 10 having such a structure also exhibits a high critical current density, the compound 10 is suitable as a material for a superconducting bulk body. An example of a superconducting compound containing an Fe element is a compound obtained by replacing a part of the elements constituting the compound represented by the chemical formula AeAFe4As4 with other elements. These compounds will be described below.
[0039] An example of compound 10 is the compound of formula Ae 1-x A xCompounds represented by Fe2As2 are exemplified. In the formula, Ae is at least one element selected from Ca, Sr, and Ba. Also, in the formula, A is at least one element selected from K, Rb, and Cs. Also, in the formula, x is a number within the range of 0 < x < 1. The crystal structure of Compound 10 having such a configuration has a space group of body-centered tetragonal I4 / mmm and has a ThCr2Si2 structure.
[0040] As another example of Compound 10, a compound represented by the chemical formula Ae(Fe 1-y Tm y )2As2 is exemplified. In the formula, Ae is at least one element selected from Ca, Sr, and Ba. Also, in the formula, Tm is at least one element selected from Co, Ni, Ru, Rh, Pd, Ir, and Pt. Also, in the formula, y is a number within the range of 0 < y < 1. The crystal structure of Compound 10 having such a configuration has a space group of body-centered tetragonal I4 / mmm and has a ThCr2Si2 structure.
[0041] As another example of Compound 10, a compound represented by the chemical formula AeFe2(As 1-z P z )2 is exemplified. In the formula, Ae is at least one element selected from Ca, Sr, and Ba. Also, in the formula, z is a number within the range of 0 < z < 1. The crystal structure of Compound 10 having such a configuration has a space group of body-centered tetragonal I4 / mmm and has a ThCr2Si2 structure.
[0042] As another example of Compound 10, a compound represented by the chemical formula LnFeAs(O,F) is exemplified. In the formula, Ln is at least one element selected from Y, La, Ce, Pr, Nd, Sm, Eu, Gd, and Dy. The crystal structure of Compound 10 having such a configuration has a space group of tetragonal P4 / nmm and has a ZrCuSiAs structure.
[0043] Another example of compound 10 is a compound represented by the chemical formula Fe(Se,Te). Compound 10 having such a structure has a tetragonal P4 / nmm space group and a PbO structure.
[0044] <Overview of bulk superconductors> Referring to FIG. 1, a superconducting bulk B which is a polycrystal of an iron-based superconductor, which is a compound 10, will be described.
[0045] As shown in Fig. 1(a), the superconducting bulk B has a disk-like shape with a thickness tb and a diameter db. The superconducting bulk B also has two main surfaces B1 and B2 that are parallel and facing each other. Fig. 1(a) shows an x-axis and a y-axis that are perpendicular to each other along a plane in which the disk-like shape extends, a z-axis that is perpendicular to the x-axis and y-axis, and a normal direction NB to the main surfaces B1 and B2.
[0046] The thickness tb of the superconducting bulk body B is preferably 1 mm or more, and preferably thicker, from the viewpoint of realizing a suitable mechanical strength for practical use as a superconductor, such as a superconducting bulk magnet, etc. The upper limit of the thickness tb of the superconducting bulk body B is not limited from the viewpoint of mechanical strength.
[0047] Although not limited thereto, when utilized as a superconducting bulk magnet, the superconducting bulk B captures magnetic flux such that the superconducting bulk B is magnetized along the normal direction NB, i.e., the thickness direction.
[0048] The shape of the superconducting bulk B is not limited to the disk-like shape shown in FIG. 2. Other examples of the shape of the superconducting bulk B include a plate-like shape having two parallel main surfaces facing each other, and having a ring shape, a square shape, a rectangle or other polygonal shape, or any other shape when viewed in a plan view from the thickness direction. The relationship between the thickness tb and the diameter db can be appropriately set depending on the application. For example, when the superconducting bulk B is used as a magnet by cooling it in a magnetic field, it is preferable that tb>db.
[0049] (Degree of crystal grain orientation in bulk superconductors) 1(b), in the superconducting bulk B, a plurality of crystal grains 1 are aligned with a high degree of orientation, thereby forming an oriented texture. Due to the formation of the oriented texture, the superconducting bulk B exhibits a critical current density Jc that is improved compared to conventional materials.
[0050] The degree of orientation can be expressed using the degree of c-axis orientation of the superconducting bulk body B as measured by Lotgering's method as a scale. The degree of c-axis orientation of the superconducting bulk body B as measured by Lotgering's method is 0.2 or more. Moreover, from the viewpoint of further improving the critical current density Jc, the degree of c-axis orientation of the superconducting bulk body B as measured by Lotgering's method is preferably 0.4 or more.
[0051] The degree of c-axis orientation according to the Lotgering method is calculated using the following formula.
[0052] F = (ρ-ρ0) / (1-ρ0) ρ=ΣI(00l) / ΣI(hkl) ρ0=ΣI0(00l) / ΣI0(hkl) In the formula, F indicates the degree of orientation of the c-axis according to the Lotgering method. ΣI0(00l) and ΣI(00l) respectively indicate the sum of the intensities of the peaks corresponding to the (00l) direction in the X-ray diffraction (XRD) patterns of the superconducting bulk B and a sample with no oriented texture, such as a powder sample, having the same chemical composition as the superconducting bulk B. ΣI0(hkl) and ΣI(hkl) respectively indicate the sum of the intensities of all peaks in the X-ray diffraction (XRD) patterns of the superconducting bulk B and a sample with no oriented texture, such as a powder sample, having the same composition as the superconducting bulk B.
[0053] 1(b), in the superconducting bulk B, a plurality of crystal grains 1 are aligned so that the extending direction of the plate-like shape of the crystal grain 1 (the ab-plane direction of the crystal grain 1) corresponds to the extending direction of the disk-like shape of the superconducting bulk B (the in-plane direction of the main surfaces B1, B2). In other words, in each crystal grain 1, the normal direction NB of the main surfaces B1 and B2 of the superconducting bulk B corresponds to the c-axis direction of the crystal structure constituting the crystal grain 1.
[0054] In this embodiment, the degree of agreement between the normal direction NB and the c-axis direction of each crystal grain 1 is expressed by the degree of orientation of the c-axis according to the Lotgering method. The higher the degree of orientation of the c-axis in the superconducting bulk B, the more the critical current density Jc of the superconducting bulk B can be improved.
[0055] (Other configurations of bulk superconductors) The superconducting bulk B may contain at least one element selected from the group consisting of low-melting-point metals tin, gallium, and indium, in addition to the multiple crystal grains 1. Although not limited thereto, it is preferable that the superconducting bulk B contains the above-mentioned low-melting-point metal at the interfaces between the crystal grains 1, i.e., at least a portion of the grain boundaries. With this configuration, the low-melting-point metal strengthens the electrical bond between the crystal grains 1 at the grain boundaries, thereby further improving the critical current density Jc of the superconducting bulk B.
[0056] Furthermore, the superconducting bulk body B may be impregnated with a resin such as an epoxy resin. The surface of the superconducting bulk body B may be coated with a resin. The resin used for coating may be a reinforced resin containing carbon fiber or the like, or may be a simple resin. With these configurations, the mechanical strength of the superconducting bulk body B can be increased.
[0057] In the bulk superconductor B, oxides are distributed in islands at some of the grain boundaries. In general, oxides that are continuously distributed at the grain boundaries so as to surround each crystal grain 1 are generated due to oxygen contamination during the manufacturing process, and can be a factor in reducing the critical current density Jc of the bulk superconductor. However, in the bulk superconductor B, oxides are distributed in discontinuous islands at the grain boundaries, so that at least some of the grain boundaries are joined to each other without the oxide. Furthermore, the junctions between the crystal grains 1 are formed by the ab planes of the crystal structure. Therefore, this junction does not inhibit the superconducting current generated inside the bulk superconductor B. Therefore, the bulk superconductor B can exhibit a high critical current density Jc even when it contains oxides.
[0058] <Effects of bulk superconductors> As described above, the superconducting bulk B is a polycrystal of an iron-based superconductor, and has a degree of c-axis orientation of 0.2 or more as measured by the Lotgering method.
[0059] According to this configuration, since the multiple crystal grains 1 are aligned with a high degree of orientation in the superconducting bulk B, the suppression of the critical current density caused by the randomness of the crystal orientation is reduced. Therefore, the superconducting bulk B can effectively utilize the potential of the single crystal of the iron-based superconductor and can exhibit a critical current density Jc that is improved compared to the conventional case.
[0060] Moreover, the degree of orientation of the c-axis is preferably 0.4 or more.
[0061] With this configuration, the superconducting bulk body B can better utilize the potential of the single crystal of the iron-based superconductor, and can exhibit a critical current density Jc that is improved compared to the conventional art.
[0062] It is preferable that the superconducting bulk B has a disk-like shape, and the normal direction NB of the principal surfaces B1 and B2 corresponds to the orientation direction of the c-axis.
[0063] According to this configuration, it is possible to further improve the critical current density Jc when the superconducting bulk B captures magnetic flux so that the superconducting bulk B is magnetized along the normal direction NB.
[0064] The thickness tb of the superconducting bulk B is preferably 1 mm or more.
[0065] With this configuration, it is possible to realize a superconducting bulk body B having mechanical strength suitable for practical use as a superconductor, such as a superconducting bulk magnet.
[0066] The superconducting bulk B preferably contains at least one element selected from tin, gallium, and indium.
[0067] According to this configuration, the low-melting point metal strengthens the electrical bonds between the crystal grains 1 at the grain boundaries, so that the critical current density Jc of the superconducting bulk body B is further improved.
[0068] Compound 10, which is an iron-based superconductor, is a compound represented by the chemical formula AeAFe4As4, in which Ae is preferably at least one element selected from Ca, Sr, and Ba, and A is preferably at least one element selected from K, Rb, and Cs.
[0069] With this configuration, the single crystal of compound 10 exhibits a high critical current density Jc, and therefore the polycrystalline superconducting bulk also exhibits a high critical current density Jc.
[0070] Second Embodiment <Manufacturing method of bulk superconductor> A manufacturing method M10 according to a second embodiment of the present invention will be described with reference to FIG. 3 and FIG. 4. For convenience of description, the same reference numerals are used for components having the same functions and configurations as those described in the first embodiment, and the description thereof will not be repeated. FIG. 3 is a flow chart showing the flow of the manufacturing method M10. FIG. 4(a) is a cross-sectional view showing the pellet P after the preliminary sintering step S13 included in the manufacturing method M10 is performed. FIG. 4(b) is a cross-sectional view showing the pellet P before the main sintering step S14 included in the manufacturing method M10 is performed. FIG. 4(c) is a cross-sectional view showing the superconducting bulk body B after the main sintering step S14 is performed. FIG. 4(d) is a cross-sectional view showing the pellet P obtained by the preliminary sintering step S13. FIG. 4(e) is a cross-sectional view showing the superconducting bulk body B obtained by the main sintering step S14.
[0071] The manufacturing method M10 is a method for manufacturing a superconducting bulk body B. As shown in Fig. 3, the manufacturing method M10 includes a mixing step S11, a firing step S12, a pre-sintering step S13, and a main sintering step S14.
[0072] (Mixing process) The mixing step S11 is a step of mixing, as starting materials, each element constituting compound 10 or compounds containing each of the elements constituting compound 10. By carrying out the mixing step S11, a mixture of the starting materials is obtained.
[0073] The starting material may be each element constituting compound 10, which is a compound represented by the chemical formula AeAFe4As4, or a compound containing each of the elements constituting compound 10. In the formula, Ae is at least one element selected from Ca, Sr, and Ba, and A is at least one element selected from K, Rb, and Cs. In this embodiment, Ca is selected as Ae, and K is selected as A. By selecting Ca as Ae and K as A, a commercially available product can be obtained at a low cost as the starting material.
[0074] Each of the starting materials is preferably in powder form. By each of the starting materials being in powder form, it becomes easy to mix uniformly in the mixing step S11. The starting materials may be prepared in advance in the form of a powder, or may be pulverized in the mixing step S11 to become in the form of a powder.
[0075] The mixing step S11 is not particularly limited as long as it is a step of mixing the starting materials, but is preferably performed in an inert gas atmosphere. By performing the mixing step S11 in an inert gas atmosphere, it is possible to reduce the deterioration of the starting materials, which is mainly caused by contamination of the starting materials by oxygen in the mixing step S11. Examples of the inert gas include nitrogen gas and argon gas. The inert gas atmosphere can be achieved by filling a glove box with an inert gas, but is not limited thereto.
[0076] The tool used in the mixing step S11 is not particularly limited as long as it is a tool capable of mixing the starting materials. For example, a mortar can be used as the tool.
[0077] (Firing process) The calcination step S12 is a step of calcining the mixture of starting materials, and is carried out by heating a container in which the mixture is sealed. By carrying out the calcination step S12, a polycrystalline powder containing a plurality of crystal grains 1 made of compound 10 is obtained.
[0078] In the calcination step S12, the heating temperature and heating time can be appropriately set according to the type of compound 10. When compound 10 is a compound represented by the chemical formula CaKFe4As4 as in this embodiment, the heating temperature is preferably 800°C or higher and preferably 1000°C or lower. The heating time is preferably 1 hour or longer. By setting the heating time to 1 hour or longer, the mixture can be sufficiently calcined. The heating time is preferably 10 hours or shorter. This is because there is no significant difference in the calcined product obtained even if the heating time is longer than 10 hours. In this embodiment, the heating temperature is 930°C and the heating time is 5 hours.
[0079] The container used for carrying out the firing step S12 may be any container capable of firing. The container used is preferably made of a material that does not easily react with the elements contained in the mixture and oxygen at a temperature of 1000° C. or higher. A preferred material is stainless steel.
[0080] The heating method used to carry out the firing step S12 can be appropriately selected. In this embodiment, an electric furnace is used as the heating method.
[0081] (Pre-sintering process) The pre-sintering step S13 is a step of sintering the polycrystalline powder, and is performed by heating and pressurizing a container in which the polycrystalline powder is sealed. By performing the pre-sintering step S13, a pellet P, which is a provisionally sintered body including a plurality of crystal grains 1P, is obtained.
[0082] An overview of the preliminary sintering step S13 will be described with reference to Fig. 4(a). Fig. 4(a) shows a cylinder S1 with a circular inner shape, pistons P11 and P12 inserted from two openings at both ends of the cylinder S1, and a cavity C1 formed by the cylinder S1 and the pistons P11 and P12. A container sealing polycrystalline powder is placed in the cavity C1. Heat is applied to the container via the cylinder S1, and molding pressure Pr is applied via the pistons P11 and P12, whereby the polycrystalline powder inside the container is sintered to obtain a pellet P.
[0083] With reference to FIG. 4(d), the pellet P obtained by the preliminary sintering step S13 will be outlined. The pellet P has a cylindrical shape with a thickness tp and a diameter dp, and has two parallel principal surfaces P1 and P2 facing each other. In FIG. 4(d), a normal direction NP that is a normal direction to the principal surfaces P1 and P2 is illustrated. As shown in FIG. 4(d), the pellet P includes a plurality of crystal grains 1P. In the pellet P, the plurality of crystal grains 1P are arranged with high randomness, and therefore no oriented structure is formed.
[0084] In the pre-sintering step S13, the heating temperature and heating time can be appropriately set according to the type of compound 10. For example, when compound 10 is a compound represented by the chemical formula CaKFe4As4, the heating temperature is preferably higher than 600°C, and more preferably near 700°C. The heating time is preferably 3 minutes or more. By setting the heating time to 3 minutes or more, a pellet P having a high density can be obtained by pre-sintering. The heating time is preferably 1 hour or less. This is because there is no significant difference in the density of the pellet P obtained even if the heating time is longer than 1 hour. In this embodiment, 700°C is adopted as the heating temperature, and 10 minutes is adopted as the heating time.
[0085] In the preliminary sintering step S13, the molding pressure applied to the container can be appropriately set according to the type of compound 10. For example, when compound 10 is a compound represented by the chemical formula CaKFe4As4, the molding pressure is preferably 10 MPa or more and 200 MPa or less. In this embodiment, the molding pressure is 50 MPa.
[0086] The container used to carry out the preliminary sintering step S13 may be any container capable of applying heat and pressure. The container used is preferably made of a material that is unlikely to react with the elements contained in the mixture, oxygen, and inert gases at a temperature of 1000°C or higher. A preferred example of the container used includes a graphite container. The container used to carry out the preliminary sintering step S13 may be the same container as the container used to carry out the firing step S12, or may be a different container.
[0087] The heating and pressing method used to carry out the pre-sintering step S13 may be a conventionally known method, examples of which include a spark plasma sintering (SPS) method and a hot pressing method.
[0088] Furthermore, for reasons that will be described later, in the pre-sintering step S13, before the heating and pressing, at least one element selected from the group consisting of low-melting point metals tin, gallium, and indium may be added to the polycrystalline powder.
[0089] (Main sintering process) The sintering step S14 is a step of obtaining a superconducting bulk body B by sintering the pellet P, which is a provisionally sintered body, while applying uniaxial pressure along the normal direction NP of the main surfaces P1 and P2 and so as to increase the ratio of the main surface size of the pellet P to the thickness tp of the pellet P. Although not limited thereto, the sintering step S14 is performed by heating and pressurizing a container in which the pellet P is sealed using uniaxial pressure.
[0090] As used herein, "main surface size" means the length representing the size of the main surface. Specifically, (i) when the main surface is circular or ring-shaped, it means the diameter of the circle or the outer diameter of the ring; (ii) when the main surface is square, it means the length of one side of the square; and (iii) when the main surface has a shape other than circular, ring-shaped, and square, it means the square root of the area of the main surface. In the second embodiment, in the superconducting bulk body B and the pellet P which is its precursor, since the main surfaces B1, B2, P1, and P2 are all circular, the main surface size of the superconducting bulk body B is the diameter db, and the main surface size of the pellet P is the diameter dp.
[0091] Referring to FIGS. 4(b) and 4(c), the outline of this sintering process S14 will be described. In FIG. 4(b), a cylinder S2 with a circular inner shape, pistons P21 and P22 inserted from two openings at both ends of the cylinder S2, and a cavity C2 formed by the cylinder S2 and the pistons P21 and P22 are illustrated. In the cavity C2, the pellet P is arranged such that the normal directions NP of the main surfaces P1 and P2 are along the directions in which the pistons P21 and P22 move in the piston movement, that is, the z-axis direction. The pellet P is sintered while being uniaxially pressed by a molding pressure Pr applied through the pistons P21 and P22 in the cavity C2. Thereby, the superconducting bulk body B is obtained from the pellet P which is a green compact.
[0092] As shown in FIG. 4(c), when a molding pressure Pr is applied to the pellet P through the pistons P21 and P22 by uniaxial pressing along the normal direction NP, that is, the z-axis, the pellet P deforms so that the ratio of the main surface size dp to the thickness tp increases. As a result, a superconducting bulk body B having a disk shape with a thickness tb and a diameter db as shown in FIG. 4(e) is obtained. Here, regarding the main surface size with respect to the thickness of the pellet P and the superconducting bulk body B, there is a relationship shown in the following formula (i). dp / tp < tb / db Formula (i)
[0093] The deformation of the pellet P promotes the formation of an oriented structure of the crystal grains 1P inside the pellet P. Specifically, as shown in (d) and (e) of FIG. 4, the multiple crystal grains 1P move parallel and rotate, and are aligned, so that the normal direction of the plate-shaped main surface of the crystal grains 1P approaches the z-axis, which is the pressure direction. This alignment results in a superconducting bulk B in which the normal direction NB of the main surfaces B1 and B2 corresponds to the normal direction of the main surface of the crystal grain 1, i.e., the c-axis direction of the crystal structure constituting the crystal grain 1. The superconducting bulk B obtained in this way can exhibit a critical current density Jc that is improved compared to conventional methods.
[0094] It is presumed that the above-mentioned alignment is a unique phenomenon that occurs when pellet P containing multiple crystal grains 1P is uniaxially pressed with deformation. Specifically, it is presumed that even if pellet P not containing crystal grains 1P is sintered by uniaxially pressing with deformation, the generation of crystal grains is inhibited by the deformation, and therefore pellet P containing a sufficient amount of crystal grains 1P cannot be obtained. Also, even when pellet P containing crystal grains 1P is uniaxially pressed without deformation, it is presumed that alignment of crystal grains 1P is not promoted and a sufficient oriented structure is not formed.
[0095] In the sintering step S14, the pellet P preferably contains at least one element selected from low-melting-point metals tin, gallium, and indium. With this configuration, the low-melting-point metal acts as a lubricant to promote the alignment of the crystal grains 1P described above, and in the resulting superconducting bulk B, the electrical bonds between the crystal grains 1 at the grain boundaries are strengthened, thereby further improving the critical current density Jc of the superconducting bulk B.
[0096] In this sintering step S14, the cavity size of the cavity C2 is larger than the main surface size dp of the pellet P. According to this configuration, the pellet P is deformed by uniaxial pressure so as to extend along the tangential direction of the main surfaces P1 and P2, so that the alignment of the crystal grains 1P inside the pellet P is further promoted. Therefore, the degree of orientation in the obtained superconducting bulk body B is further improved. As used herein, the term "cavity size" means a length representative of the size of the cavity, specifically, (i) when the shape of the cavity when viewed in a plane along the z-axis direction (hereinafter referred to as the "planar shape of the cavity") is circular, it means the diameter of the circle, (ii) when the planar shape of the cavity is square, it means the length of one side of the square, and (iii) when the planar shape of the cavity is a shape other than a circle or a square, it means the square root of the area of the planar shape of the cavity.
[0097] In addition, in the sintering step S14, some of the crystal grains 1P and some of the oxides present at the grain boundaries are pulverized by uniaxial pressing. Then, as the pellet P deforms, the small pieces resulting from the pulverization move. Therefore, the oxides present at the grain boundaries are present continuously surrounding each of the crystal grains 1P before the sintering step S14, but are present in a discontinuous island-like distribution due to the crushing and movement after the sintering step S14. Therefore, the area where the crystal grains 1P are joined together without the oxide increases before and after the sintering step S14, so that the resulting superconducting bulk body B can exhibit a high critical current density Jc.
[0098] The container used to carry out the main sintering step S14 may be any container capable of heating and pressurizing, and may be, for example, the same container as the container used to carry out the preliminary sintering step S13. The container may be sealed to such an extent that the pellets P contained therein do not flow out when subjected to uniaxial pressing. Therefore, the container does not need to be subjected to the complicated processing required when using isostatic pressing, such as metal coating using silver wrap and stainless steel pipes, and end welding of the coating. Therefore, the main sintering step S14 can be carried out easily.
[0099] In this sintering step S14, the heating temperature and heating time can be appropriately set according to the type of compound 10. For example, when compound 10 is a compound represented by the chemical formula CaKFe4As4, the heating temperature is preferably higher than 600°C, and more preferably around 700°C, without being limited thereto. The heating time is preferably 3 minutes or more. By setting the heating time to 3 minutes or more, the deformation of the pellet P can be sufficiently promoted. The heating time is preferably 1 hour or less. By setting the heating time to 1 hour or less, a superconducting bulk body B with sufficient mechanical strength can be manufactured without spending extra time.
[0100] In the sintering step S14, the molding pressure can be appropriately set according to the type of compound 10. For example, when compound 10 is a compound represented by the chemical formula CaKFe4As4, the molding pressure is preferably 10 MPa or more and 200 MPa or less. In this embodiment, 50 MPa is used as the molding pressure. In addition, in the sintering step S14, the pressurizing time can be determined independently of the above-mentioned heating time. In this embodiment, the pressurizing time is set to be equal to the heating time. That is, in the sintering step S14 of this embodiment, heating and pressurizing are performed simultaneously.
[0101] In the sintering step S14, the method used to sinter the pellets P while applying uniaxial pressure may be a conventionally known method. In other words, the sintering step S14 can be performed by utilizing existing manufacturing equipment that is owned by the manufacturer and capable of applying uniaxial pressure. Therefore, the sintering step S14 is suitable for both small-scale and large-scale production, and the equipment cost is low. Examples of the method used to sinter the pellets P while applying uniaxial pressure include a spark plasma sintering (SPS) method, a hot press method, and an extrusion molding method.
[0102] The atmosphere in which each of steps S11 to S14 is carried out is preferably a high-purity inert gas. By carrying out this sintering step S14 in a high-purity inert gas, the critical current density Jc of the resulting superconducting bulk body B can be further increased. The type of inert gas can be appropriately determined in consideration of the inertness and cost of the gas. Furthermore, the higher the purity of the inert gas, the more preferable it is. It is preferable that the O2 and H2O contained in the impurity gas are both less than 1 ppm. However, the purity of the inert gas can be appropriately determined in consideration of cost-effectiveness.
[0103] <Effects of manufacturing method for bulk superconductors> As described above, manufacturing method M10 is a method for manufacturing a superconducting bulk body B, which is a polycrystal of an iron-based superconductor, and includes a sintering step S14 in which a pellet P, which is a pre-sintered body, is sintered while applying uniaxial pressure along the normal direction NP of the main surfaces P1 and P2, and so that the ratio of the main surface size of the pellet P to the thickness tp of the pellet P is increased, thereby obtaining a superconducting bulk body B.
[0104] This configuration promotes the formation of an oriented structure in the multiple crystal grains 1P contained in the pellet P. As a result, it is possible to produce a bulk superconductor B that satisfactorily utilizes the potential of a single crystal of an iron-based superconductor and exhibits a critical current density that is higher than that of conventional bulk superconductors.
[0105] In the main sintering step S14, the pellet P is sintered while being uniaxially pressed in the cavity C2, and the cavity size of the cavity C2 is preferably larger than the size of the main surface.
[0106] According to this configuration, the uniaxial pressurization causes the pellet P to deform so as to elongate along the tangential direction of the main surfaces P1 and P2, which further promotes the alignment of the crystal grains 1P inside the pellet P. Therefore, the degree of orientation in the obtained superconducting bulk B is further improved.
[0107] In the main sintering step S14, it is preferable to sinter the pellet P while applying uniaxial pressure using a spark plasma sintering method or a hot press method.
[0108] According to this configuration, it is possible to realize the main sintering step S14 that is suitable for both small-scale and large-scale production and requires low equipment costs.
[0109] The pellet P preferably contains at least one element selected from tin, gallium and indium.
[0110] With this configuration, the low-melting point metal acts as a lubricant to promote the alignment of the above-mentioned crystal grains 1P, and in the resulting superconducting bulk B, the electrical bonding between the crystal grains 1 at the grain boundaries is strengthened, thereby further improving the critical current density Jc of the superconducting bulk B.
[0111] The pellet P preferably comprises a compound represented by the chemical formula AeAFe4As4, where Ae is at least one element selected from Ca, Sr, and Ba, and A is at least one element selected from K, Rb, and Cs.
[0112] According to this configuration, the manufacturing process is simplified and the superconducting bulk body B can be manufactured at low cost.
[0113] <Modification> The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention.
[0114] For example, the production method M10 according to the second embodiment may further include a weighing step of weighing each of the compounds as starting materials before the above-mentioned mixing step S11. EXAMPLES
[0115] The first and second examples of the present invention, the first reference example of the present invention, and the first and second comparative examples of the present invention will be described with reference to Figs. 5 to 8. Fig. 5 is a graph showing X-ray diffraction (XRD) patterns of the superconducting bulk bodies of the first and second examples of the present invention, the small pieces of the first reference example, the pellets of the first comparative example, and the powders of the second comparative example. The upper part of Fig. 6 is an SEM image and an EBSD map of the cross section of the pellets of the first comparative example shown in Fig. 5. The lower part of Fig. 6 is an SEM image and an EBSD map of the cross section of the bulk body of the second example shown in Fig. 5. The upper part of Fig. 7 is an SEM image and an EDX map of the cross section of the pellets of the first comparative example shown in Fig. 5. The lower part of Fig. 7 is an SEM image and an EDX map of the cross section of the bulk body of the second example shown in Fig. 5. Fig. 8 is a graph showing the applied magnetic field dependence of the critical current density shown by the superconducting bulk body of the second example shown in Fig. 5 and the pellets of the first comparative example.
[0116] <Production of bulk superconductors> [First embodiment] (Mixing process) As starting materials, commercially available powders of Ca element (purity > 99.5 mol%), K element (purity > 99.5 mol%), Fe element (purity > 99.9 mol%), and As element (purity > 99.9999 mol%) were prepared. To obtain the precursors of arsenide compounds, CaAs, KAs, and Fe2As, the elements contained in each precursor were selected from the starting materials and mixed. The obtained precursors of arsenide compounds, CaAs, KAs, and Fe2As, were mixed in a molar ratio of CaAs:KAs:Fe2As = 1:1.05:2 to obtain a powder mixture.
[0117] (Firing process) The powder mixture was then sealed in a stainless steel container. The mixing of the starting materials and the sealing of the powder mixture were carried out in a glove box with an inert gas atmosphere (O2<1ppm, H2O<1ppm). The stainless steel container with the sealed powder mixture was then fired in an electric furnace to obtain polycrystalline powder. The firing heating temperature and heating time were 930°C and 5 hours, respectively.
[0118] (Pre-sintering process) The polycrystalline powder was filled into a graphite container with an inner diameter of 10 mm. The graphite container was then heated and pressurized using the SPS method to sinter the polycrystalline powder and obtain a pellet with a diameter of 10 mm. The heating temperature, heating time, and molding pressure for the heating and pressing were 700°C, 10 minutes, and 50 MPa, respectively.
[0119] (Main sintering process) The resulting pellet with a diameter of 10 mm was placed in a graphite container with an inner diameter of 20 mm. Therefore, the cavity size of the graphite container was larger than the main surface size of the pellet. The graphite container was then heated and pressurized by uniaxial pressing using the SPS method to deform and sinter the pellet, thereby obtaining the superconducting bulk body of the first embodiment. The heating temperature, heating time, and molding pressure were 700°C, 10 minutes, and 3 MPa, respectively. The pellet before uniaxial pressing had a thickness of 5.1 mm, and the superconducting bulk body of the first embodiment after uniaxial pressing had a thickness of 2.2 mm.
[0120] [Second embodiment] The superconducting bulk bodies of the second embodiment were obtained using the same method as the first embodiment, except that the molding pressure in this sintering process and the thickness of the superconducting bulk body after uniaxial processing were changed as shown in Table 1. Note that the difference in the thickness of the pellet before uniaxial pressing between the first and second embodiments is due to the operational error of the manufacturing equipment.
[0121] Table 1 shows the molding pressure in the main sintering process in the first and second examples, as well as the thicknesses of the pellets before uniaxial processing and the superconducting bulk bodies after uniaxial processing.
[0122] [First Reference Example] An attempt was made to manufacture the superconducting bulk body of the first reference example using the same method as in the first embodiment, except that the molding pressure in this sintering process and the thickness of the superconducting bulk body after uniaxial processing were changed as shown in Table 1. However, in the first reference example, the pellet was crushed during the sintering process, so small pieces of the first reference example were obtained instead of the superconducting bulk body.
[0123] [First Comparative Example] Except for not carrying out the main sintering step, pellets having a diameter of 10 mm were obtained by a pre-sintering step as pellets of the first comparative example using the same method as in the first embodiment. That is, as the sintering step, only the pre-sintering step using a molding pressure of 50 MPa was carried out.
[0124] [Second Comparative Example] A polycrystalline powder was obtained by a firing process as a powder of the second comparative example using the same method as in the first example, except that the pre-sintering process and the main sintering process were not performed.
[0125] (Evaluation of the degree of c-axis orientation) In order to evaluate the degree of orientation of the c-axis, XRD measurements were performed on the superconducting bulk bodies of the first and second examples, the small piece of the first reference example, the pellet of the first comparative example, and the powder of the second comparative example. The obtained XRD patterns are shown in FIG. 5. In the XRD patterns shown in FIG. 5, the stars represent peaks derived from the compound represented by the chemical formula CaKFe4As4, the inverted triangles represent peaks derived from the compound represented by the chemical formula CaFe2As2, and the circles represent peaks derived from the compound represented by the chemical formula FeAs.
[0126] Furthermore, the degree of orientation of the c-axis was calculated by the Lotgering method for the superconducting bulk bodies of the first and second examples, the small piece of the first reference example, and the pellet of the first comparative example. The calculation results are shown in Table 1.
[0127] Furthermore, to evaluate the formation of oriented texture, scanning electron microscope (SEM) images of the cross sections of the superconducting bulk of the second embodiment and the pellet of the first comparative example were taken, along with electron backscatter diffraction (EBSD) maps of the corresponding cross sections. The results are shown in Figure 6. In Figure 6, the gray scale shown in the upper right corresponds to the crystal orientation of the crystal grains shown in the EBSD map.
[0128] (Evaluation of oxide distribution) In order to evaluate the distribution of oxides present at the grain boundaries, scanning electron microscope (SEM) images of the cross sections of the superconducting bulk of the second embodiment and the pellet of the first comparative example were taken, along with energy dispersive X-ray (EDX) maps of the corresponding cross sections. The results are shown in Figure 7. In the EDX maps shown in the right column of Figure 7, the areas where oxides are distributed are shown in a lighter shade.
[0129] (Evaluation of critical current density) The applied magnetic field dependence of the critical current density Jc of the superconducting bulk of the second embodiment and the pellet of the first comparative example was measured at a temperature of 4.2 K (absolute temperature). The measurement results are shown in Figure 8. Table 1 shows the critical current density Jc at a temperature of 4.2 K and an applied magnetic field of 5 T of the superconducting bulk of the first and second embodiments and the pellet of the first comparative example.
[0130] [Table 1]
[0131] <Consideration> As shown in FIG. 5, each of the superconducting bulk bodies of the first and second examples obtained by carrying out this sintering process showed a peak corresponding to the (002) direction of the crystal structure constituted by the compound represented by the chemical formula CaKFe4As4 at around 2θ=14 degrees. Moreover, the intensity of these peaks was greater than the intensity of the corresponding peaks of the pellet of the first comparative example obtained without carrying out this sintering process and the powder of the second comparative example. Specifically, as shown in Table 1, each of the superconducting bulk bodies of the first and second examples showed a high degree of c-axis orientation of 0.4 or more. This indicates that by carrying out this sintering process, the crystal grains contained in the pellets were aligned with a high degree of orientation, and an oriented structure was formed.
[0132] As shown in Fig. 6, the bulk superconducting body of the second embodiment had more crystal grains whose c-axes were oriented in the pressure direction than the bulk superconducting body of the first comparative example. This indicates that by carrying out this sintering process, the crystal grains were aligned with a high degree of orientation and were aligned so that the normal direction of the main surface of the bulk superconducting body corresponded to the orientation direction of the c-axes.
[0133] As shown in FIG. 7, in the pellet of the first comparative example, the oxides were continuously distributed at the grain boundaries. In contrast, in the superconducting bulk of the second example, the oxides were distributed in an island-like manner. Furthermore, the crystal grains contained in the superconducting bulk of the second example were more finely ground and had a smaller grain size than the crystal grains contained in the pellet of the first comparative example. This indicates that by carrying out this sintering process, some of the crystal grains and some of the oxides were ground and moved, localizing the oxides and promoting bonding between crystal grains without the oxides being interposed.
[0134] As shown in Fig. 8, the superconducting bulk of the second embodiment exhibited an improved critical current density Jc than the pellet of the first comparative example under conditions of 4.2 K and 0.5 T to 5 T. As shown in Table 1, the superconducting bulk of the first embodiment also exhibited an improved critical current density Jc. This shows that a superconducting bulk that is a polycrystalline iron-based superconductor and has a c-axis orientation of 0.2 or more according to the Lotgering method exhibits a critical current density Jc that is improved compared to conventional bulks.
[0135] As shown in Table 1, in the first and second examples, the higher the processing rate in the sintering process, the higher the degree of c-axis orientation tended to be. Furthermore, the evaluation results of the superconducting bulk bodies of the first and second examples suggested that the higher the degree of c-axis orientation, the higher the critical current density Jc. Furthermore, although not shown in the figures, the superconducting bulk bodies of the first and second examples had mechanical strength suitable for practical use. [Explanation of symbols]
[0136] B. Bulk superconductor B1,B2 main surface NB normal direction 1 Grain P Pellet P1,P2 main surface C1, C2 cavity
Claims
1. A bulk superconductor which is a polycrystal of an iron-based superconductor and has a degree of c-axis orientation of 0.2 or more as measured by the Lotgering method.
2. The superconducting bulk body according to claim 1 , wherein the degree of orientation is 0.4 or more.
3. It has a disk-like shape, and A superconducting bulk body as described in claim 1 or 2, wherein the normal direction of the main surface corresponds to the orientation direction of the c-axis.
4. The superconducting bulk body according to claim 3, having a thickness of 1 mm or more.
5. A bulk superconductor according to any one of claims 1 to 4, comprising at least one element selected from tin, gallium and indium.
6. The iron-based superconductor has the chemical formula AeAFe 4 A.S. 4 The compound is represented by the formula: Ae is at least one element selected from Ca, Sr, and Ba; 6. A bulk superconductor according to claim 1, wherein A is at least one element selected from K, Rb, and Cs.
7. A method for producing a polycrystalline bulk superconductor of an iron-based superconductor, comprising the steps of: A manufacturing method including a sintering step in which a pellet, which is a pre-sintered body, is sintered while applying uniaxial pressure along the normal direction of its main surface so that the ratio of the size of the main surface of the pellet to its thickness becomes large, thereby obtaining the superconducting bulk body.
8. 8. The manufacturing method according to claim 7, wherein in the main sintering step, the pellet is sintered while being uniaxially pressed in a cavity, and the cavity size is larger than the size of the main surface.
9. 9. The method according to claim 7, wherein in the main sintering step, the pellet is sintered while being uniaxially pressed by a spark plasma sintering method or a hot pressing method.
10. The method according to any one of claims 7 to 9, wherein the pellet contains at least one element selected from the group consisting of tin, gallium, and indium.
11. The pellets have the formula AeAFe 4 A.S. 4 The compound includes a compound represented by the formula: Ae is at least one element selected from Ca, Sr, and Ba; The method according to any one of claims 7 to 10, wherein A is at least one element selected from the group consisting of K, Rb, and Cs.
Citation Information
Patent Citations
Iron-based superconductor preparation method based on cold isostatic pressing and directional solidification technology
CN108728678A
Manufacture of bulky oxide superconductor
JP1998134656A
Iron-based superconducting material, and iron-based superconducting layer, iron-based superconducting tape wire, and iron-based superconducting wire comprising the material
JP2014227329A
Iron-based superconducting permanent magnet and method for manufacturing the same
JP2018512737A
Polycrystalline bulk body and method for producing the same
JP2021038435A